All the names that chance has: how oneself is discovered through the other - Silva, Adriana Gonçalves da (Revista Desassossego, 2022)
The novel All the names, published in 1997, has a relevant entry in the author's production: it happens after the remodelling of his narrative that occurred in 1995 with Blindness and is immediately prior to the Nobel Prize award. The narrative presents as protagonist an individual devastated by the boredom caused by the routine and the loneliness of his work at the General Conservatory. With a personality shaped and built by capitalist relations, chance will be responsible for putting him in contact with the unknown woman's file, which will destabilize the identity construction of a standard employee, proving that “It is necessary to leave the island in order to see the island” (SARAMAGO, 2012, p.41). In this sense, the reading intended in this article seeks to corroborate a certain frequent finding in the Saramaguian novels of this second phase, where the man is the only redeemer of himself - but that this path is almost always bestirred by the other.